Immunogenicity and safety of a trivalent inactivated influenza vaccine produced in Shenzhen, China - Zhaojun Mo; Yi Nong; Shuzhen Liu; Ming Shao; Xueyan Liao; Kerry Go; Nathalie Lavis (Taylor & Francis Group, 2017)
A split-virion trivalent inactivated influenza vaccine produced according to the Chinese pharmacopeia (Shz-IIV3) has been commercially available in China since 2014. Here, we describe the results of a phase IV open-label trial to describe the immunogenicity and safety of the 2014-2015 Northern Hemisphere formulation of Shz-IIV3 in individuals ≥ 6 months of age. Subjects 6-35 months of age received 2 half-doses of Shz-IIV3 (0.25 ml) 28 d apart, and subjects ≥ 3 y of age received a single full dose (0.5 ml). The study included 602 subjects. Except for the A (H3N2) strain in subjects 3-17 years, geometric mean hemagglutination inhibition titer ratios were ≥ 10 and rates of seroconversion/significant increase in titer were ≥ 78% in all age groups. For the H3N2 strain in subjects 3-17 years, the geometric mean titer ratio was 3.8 and the rate of seroconversion/significant increase was 56%. Post-vaccination seroprotection rates were ≥ 88% for all strains in all age groups. The most common solicited reactions were injection-site pain/tenderness and fever, most of which were grade 1 and resolved within 3 d. Vaccine-related unsolicited adverse events were reported only by subjects 6-23 months, most of which were mild abnormal crying and irritability. No vaccine-related serious adverse events and no deaths were reported. No new safety signals or unexpected safety events occurred, although an immediate anaphylactic skin reaction occurred in one subject. This study confirmed that the 2014-2015 Northern Hemisphere formulation of Shz-IIV3 was well tolerated and highly immunogenic in subjects ≥ 6 months of age.